Academic education in Public Health - Stankiewicz-Choroszucha, Bożenna; Samoliński, Bolesław (Polish Journal of Public Health, 2011)
The specialisation in Public Health is a new academic experience for the Medical University of Warsaw (MUW). The history of the specialisation began in 2000 upon the establishment of the Faculty for Health Sciences. Education standards for Public Health studies for both the first cycle academic degree – a bachelor degree and the second cycle academic degree – masters, have been specified. The graduates’ qualifications, the acquired competencies and specific skills have been described. The curricular requirements for a specialisation internship in order to receive a diploma of Public Health specialist have been compared with those concerning the education of a master in Public Health. Professional perspectives for graduates of studies in Public Health have been outlined including the positions they can hold.